The Analogies Used in Mukimi’s Works - Madalievna, Iskandarova Sharifa; Abdurahimovna, Juraeva Ramziya (European Journal of Life Safety and Stability (2660-9630), 2021)
The article analyzes the individual analogies used in the work of Mukimi, a mature representative of the Kokand literary environment.